2021
DOI: 10.1088/1755-1315/621/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of ultrasonic and ultra high frequency techniques in the partial discharge detection and positioning of gas insulated switchgear

Abstract: Partial discharge live detection of GIS can effectively find internal defects, but it is often interfered by surrounding environmental noise, which affects the correct identification and judgment of defect signals. This paper introduces the application of AE and UHF technique in the live detection of GIS, which successfully recognizes the external interference signal, analyzes the cause of abnormal partial discharge signal based on signal characteristics, and uses the method by calculating time difference to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…For example, based on Michelson interference principle, Zhou et al [14] had developed a fiber-optic ultrasonic sensor system, and the detection performance for weak ultrasonic signals was experimentally studied. Xiao et al [15] found that the interference of environmental noise could be effectively reduced with combined detection method for ultrasonic and ultrahigh frequency signals. With this method, the defect signals would be correctly identified, and the signal source would also be accurately located.…”
Section: Introductionmentioning
confidence: 99%
“…For example, based on Michelson interference principle, Zhou et al [14] had developed a fiber-optic ultrasonic sensor system, and the detection performance for weak ultrasonic signals was experimentally studied. Xiao et al [15] found that the interference of environmental noise could be effectively reduced with combined detection method for ultrasonic and ultrahigh frequency signals. With this method, the defect signals would be correctly identified, and the signal source would also be accurately located.…”
Section: Introductionmentioning
confidence: 99%